2007
DOI: 10.1590/s0074-02762007005000002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of human acute schistosomiasis with oxamniquine induces an increase in interferon-gamma response to Schistosoma mansoni antigens

Abstract: Patients with acute schistosomiasis were studied before and after oxamniquine treatment. They had been exposed to cercariae 5 to 9 weeks before, and presented compatible clinical manifestations, eosinophilia, and high levels of total IgE. Interferon-γ (IFN-γ)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
3
5
1
Order By: Relevance
“…However, treatment with either praziquantel or oxamniquine revealed similar effects on the immune response. Both praziquantel and oxamniquine caused the modulation of immune responses, a similar cytokine pattern to that shown for oxamniquine of the raised IFN-γ in those who were infected, during all the examination times, post treatment [40][41][42] . In the same individuals before treatment, raised levels of IL-4 and IL-5 were also observed, which is consistent with the dominance of IL-4, IL-5 later in chronic infections and a controlling role of IL-10 as reported by other investigators in S.japonicum 40 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, treatment with either praziquantel or oxamniquine revealed similar effects on the immune response. Both praziquantel and oxamniquine caused the modulation of immune responses, a similar cytokine pattern to that shown for oxamniquine of the raised IFN-γ in those who were infected, during all the examination times, post treatment [40][41][42] . In the same individuals before treatment, raised levels of IL-4 and IL-5 were also observed, which is consistent with the dominance of IL-4, IL-5 later in chronic infections and a controlling role of IL-10 as reported by other investigators in S.japonicum 40 .…”
Section: Discussionsupporting
confidence: 69%
“…IFN-γ is generally involved in delayed-type hypersensitivity reactions dominating in individuals having acute infections. During this period, the immune response is involved in antigen processing and mobilisation of cell-mediated immune system in which IFN-γ plays a key regulatory role 40,41 . The Th1-like cytokine phenotype observed in this study cannot be considered as inducing susceptibility to schistosome infection but may possibly indicate a regulatory role of Th1-like cytokines in the early responses to infection 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that IFN-γ levels increase in order to control the progression of hepatic fibrosis in chronic patients. In a recent study, we demonstrated increased IFN-γ production in response to SEA and SWAP stimulation after oxamniquine treatment in acute schistosomiasis patients (Souza et al 2007). In the present study, we analyzed IFN-γ production in acute patients before specific treatment.…”
Section: Discussionmentioning
confidence: 90%
“…In this context, we observed a higher number of IFN- γ + and IL-4 + T CD8 + lymphocytes in response to SEA in the ACT-TR group (Figure 4). De Souza et al [72] demonstrated—six months after specific treatment with oxamniquine—that the IFN- γ levels increased significantly in response to SEA. Similarly, it was reported that patients with chronic disease living in endemic areas showed increased levels of IFN- γ after treatment in response to parasite antigens [73].…”
Section: Discussionmentioning
confidence: 99%